2007
DOI: 10.1073/pnas.0611007104
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hydrophobic and electrostatic interactions to the membrane integration of the Shaker K + channel voltage sensor domain

Abstract: Membrane-embedded voltage-sensor domains in voltage-dependent potassium channels (K v channels) contain an impressive number of charged residues. How can such highly charged protein domains be efficiently inserted into biological membranes? In the plant Kv channel KAT1, the S2, S3, and S4 transmembrane helices insert cooperatively, because the S3, S4, and S3-S4 segments do not have any membrane insertion ability by themselves. Here we show that, in the Drosophila Shaker Kv channel, which has a more hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 39 publications
8
74
1
Order By: Relevance
“…Thus, the retention of one or more TM segments at the ER translocon to generate TM segment bundles might facilitate partitioning into the lipid phase Meindl-Beinker et al, 2006). In the case of P2X2 TM1, retention at the translocon pending the synthesis of TM2 might allow for the assembly of the two helices into a conformation that masks polar residues within TM1 (H33, R34 and Q37) and TM2 (D349), reducing the thermodynamic cost of membrane partitioning (Zhang et al, 2007). In support of this hypothesis, substitution of this highly conserved Asp for an uncharged residue in TM2 of a closely related P2X family member, caused an assembly defect and loss of function of the ion channel (Duckwitz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the retention of one or more TM segments at the ER translocon to generate TM segment bundles might facilitate partitioning into the lipid phase Meindl-Beinker et al, 2006). In the case of P2X2 TM1, retention at the translocon pending the synthesis of TM2 might allow for the assembly of the two helices into a conformation that masks polar residues within TM1 (H33, R34 and Q37) and TM2 (D349), reducing the thermodynamic cost of membrane partitioning (Zhang et al, 2007). In support of this hypothesis, substitution of this highly conserved Asp for an uncharged residue in TM2 of a closely related P2X family member, caused an assembly defect and loss of function of the ion channel (Duckwitz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, more hydrophobic residues appear to promote efficient release from the ER translocon and the incorporation of the TM segment into the membrane (Hessa et al, 2005). In the case of complex polytopic membrane proteins, this model is probably an oversimplification, and multiple additional factors, including TM segment interaction (Buck et al, 2007;Meindl-Beinker et al, 2006;Zhang et al, 2007) and membrane protein assembly Sadlish et al, 2005), have yet to be fully accounted for. A particularly fascinating facet of polytopic membrane protein integration is the phenomenon of selective TM-segment retention at the ER translocon site (Cross and High, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interaction between charged residues helps fold the channel in a proper conformation that efficiently targets the channels to the plasma membrane (31,32). Papazian and colleagues (33,34) also found that divalent ions such as nickel and magnesium can bind to the extracellular ion binding pocket formed by the negatively charged residues at S2 and S3 in ether-à-go-go K ϩ channels, decelerating activation kinetics and/or inhibition of currents.…”
mentioning
confidence: 99%
“…Some TMs appear to require the insertion of the next TM in sequence to move into the bilayer, while others do not; also, TMs sometimes leave the vicinity of the translocon during insertion but then return at a later stage, possibly to aid insertion of the subsequent TM (16,17). Recent experiments have shown that the helices of the voltage sensor of the Shaker K + channel also insert cooperatively but not individually (18). Atomic force microscopy experiments in which helices of bacteriorhodopsin are pulled out of the membrane, a process reverse to integration, show an interesting resemblance to the integration behavior; when pulled from the membrane, the helices unfold through different pathways, sometimes sequentially or pairwise (19,20).…”
mentioning
confidence: 99%